Influence of B and Nb Additions and Heat Treatments on the Mechanical Properties of Cu-Ni-Co-Cr-Si Alloy for High Pressure Die Casting Applications - Avila Salgado, Denis Ariel; Juárez Hernández, Arturo; Medina Ortiz, Fermín; Lara Banda, María del Refugio; Hernández Rodríguez, Marco Antonio Loudovic (Molecular Diversity Preservation International, 2020)
: During the high pressure die casting process (HPDC), it is necessary to develop new designs and alloys for the copper plungers. In this research, two alloys Cu-9Ni-1Co-1.6Cr-2Si-1.3Fe-0.25B wt.% (A1) and Cu-9Ni-1Co-1.6Cr-2Si-0.1Fe-0.2Nb wt.% (A2) under different heat treatments (HT) were studied. Optical microscopy technique was applied to reveal the regions of dendritic morphology, also lower Secondary Dendrite Arm Spacing (SDAS); and different grain orientations. The results reveal that the solidification sequence is primary Cu dendrites and secondary intermetallics; heat treatments increase the redistribution of alloying elements in the interdendritic regions. During the heat treatments, some precipitates were found in the grain boundary after aging heat treatments for both alloys, which were determined by X-ray diffraction. Hardness test HRB presented a decrease with the solution heat treatment and an increase with the aging heat treatments proposed for both alloys. Finally, the wear resistances for both alloys were compared with a commercial alloy C17530, with decreased A1 with B additions having the best result in the as-cast condition 4.07 × 10−4 mm3 /Nm, while for A2 with Nb additions wear resistance increased, with the best result in the one with aging heat treatment 1.69 × 10−4 mm3 /Nm while for the C17530 alloy this was 2.74 × 10−4 mm3 /Nm.